Pericytes as Key Players in Retinal Diseases: A Comprehensive Narrative Review - Fabiana D’Esposito; Francesco Cappellani; Federico Visalli; Matteo Capobianco; Lorenzo Rapisarda; Alessandro Avitabile; Ludovica Cannizzaro; Roberta Malaguarnera; Giuseppe Gagliano; Antonino Maniaci; Mario Lentini; Giuseppe Montalbano; et al. (Biology)
Pericytes, specialized mural cells surrounding microvessels, play a crucial role in maintaining vascular homeostasis and function across various organs, including the eye. These versatile cells regulate blood flow, support the integrity of the blood–retinal barrier, and contribute to angiogenesis. Recent advancements in molecular and cellular biology have revealed the heterogeneity of pericytes and their critical involvement in ocular physiology and pathology. This review provides a comprehensive analysis of pericyte functions in ocular health and their implications in diseases such as diabetic retinopathy, age-related macular degeneration, glaucoma, and retinal vein occlusion. Pericyte dysfunction is implicated in vascular instability, neurovascular coupling failure, inflammation, and pathological neovascularization, contributing to vision-threatening disorders. The review further explores recent findings on pericyte-targeted therapies, including pharmacological agents, gene therapy, and cell-based approaches, aiming to restore pericyte function and preserve ocular health.